Maximus the Confessor and the Latin West - Cattoi, Thomas,; Clarke, Kevin M., (Brill's Studies in Catholic Theology ;, 2026)
In 1941, when Hans Urs von Balthasar published his monograph on Maximus's Cosmic Liturgy, few theologians in the West had more than a passing familiarity with the thought of Maximus the Confessor (580-662). Nearly a century later, scholarship on Maximus is thriving, with new monographs and articles being published every year. If you believed that Maximus' thought was only relevant for the understanding of Eastern Christian theology, this volume will show that, in fact, Maximus' vision had a major impact on the whole arc of Western thought, from the Latin Middle Ages to the present. Far from a marginal, late-antique thinker, Maximus is key figure in the development of Christian theology, straddling the divide between East and West.